Semaglutide Therapy and Accelerated Sarcopenia in Older Adults with Type 2 Diabetes: A 24-Month Retrospective Cohort Study - Ren Q; Zhi L; Liu H (Drug Design, Development and Therapy)
Qingjuan Ren, Lei Zhi, Hongfang Liu Department of Geriatrics, Shijiazhuang People’s Hospital, Shijiazhuang, Hebei, People’s Republic of ChinaCorrespondence: Qingjuan Ren, Department of Geriatrics, Shijiazhuang People’s Hospital, Shijiazhuang, Hebei, People’s Republic of China, Email 15930170635@163.comPurpose: This study aimed to investigate changes in muscle mass and strength among older adults with type 2 diabetes who were treated with Semaglutide.Methods: This was a retrospective cohort study comparing elderly patients with type 2 diabetes receiving Semaglutide to a matched control group. Changes in muscle mass and function over 24 months were assessed. Muscle mass was measured using the appendicular skeletal muscle mass index (ASMI), while muscle function was evaluated through grip strength and gait speed measurements. Differences between the two groups and changes before and after treatment were analyzed using the t-test. Additionally, multivariable linear regression models were constructed to identify clinical predictors of accelerated muscle loss during Semaglutide treatment.Results: The study involved 220 patients treated with Semaglutide and 212 control subjects. The prevalence of sarcopenia among participants was 27.7%. Semaglutide treatment significantly reduced both body mass index and muscle mass compared to controls. Notably, divergent patterns emerged in functional measures. Grip strength initially improved but then declined in men, while it continued to decrease in women. Gait speed significantly reduced in both genders. Multivariable analysis identified Semaglutide dosage, baseline ASMI, and gait speed as independent predictors of muscle loss.Conclusion: The use of Semaglutide is associated with muscle loss and functional decline in older adults with type 2 diabetes, particularly at higher doses. This effect is especially significant in patients with sarcopenia. Consequently, it is crucial to assess the risks and benefits for each elderly patient individually and to implement appropriate monitoring and interventions. The potential for nutritional supplementation and targeted exercise regimens to counteract semaglutide-associated muscle decline merits systematic investigation.Keywords: older adults, type 2 diabetes, semaglutide, sarcopenia, muscle mass, mass strength